PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN SEBAGAI INTERVENING PADA TOKO PARADIGMA KOPI MENGANTI GRESIK - Maya Nur Janah; Sujani Sujani (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
The purpose of this research is to evaluate the influence of price and product quality on customer loyalty and consumer satisfaction as an intervening variable (Case Study at Paradigma Kopi Store in Menganti Gresik). The method used is a field survey with a questionnaire approach directly distributed to customers and consumers. A total of 96 respondents were selected using the Non-Probability Sampling method, specifically the Incidental Sampling type. From the test results, all indicator questions and variable dimensions showed adequate validity and reliability. To analyze the data, this research uses the Structural Equation Modeling (SEM) method based on PLS 4. Based on the results of this study, it shows that price and product quality have a direct influence on customer loyalty, and price and product quality also have a direct influence on satisfaction. However, satisfaction does not have a significant influence on loyalty, and satisfaction cannot mediate the relationship between price, product quality, and customer loyalty.